2020
DOI: 10.1002/joc.6635
|View full text |Cite
|
Sign up to set email alerts
|

Trends and variability of precipitation extremes in the Peruvian Altiplano (1971–2013)

Abstract: Precipitation extremes have been investigated throughout the last decades in different regions of the Andes. However, little attention has been paid to the Altiplano region (Central Andes), especially to the Peruvian Altiplano (PA) that represents a complex area and is highly vulnerable to extreme events, such as floods and droughts, driven by the strong variability of precipitation. This study focuses on the analysis of 11 extreme precipitation indices (EPIs) in the period 1971-2013. In this context, commonly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 70 publications
(131 reference statements)
2
12
0
2
Order By: Relevance
“…In contrast, during the wet summer season (DJF), the contribution of maximum 5-day precipitation to total precipitation is much lower (around 20%). In summer, precipitation is dominated by frequency rather than intensity (Huerta and Lavado-Casimiro, 2020), which is also confirmed by the high correlations of dry days and total precipitation observed in this study (Figure 8a). In austral spring (SON), precipitation is higher in northeastern than in southwestern areas as also shown by Andrade (2018), which may be related to the later start of the rainy season in the southwestern areas.…”
Section: The Seasonal Cycle Of Precipitation and Temperaturesupporting
confidence: 86%
See 4 more Smart Citations
“…In contrast, during the wet summer season (DJF), the contribution of maximum 5-day precipitation to total precipitation is much lower (around 20%). In summer, precipitation is dominated by frequency rather than intensity (Huerta and Lavado-Casimiro, 2020), which is also confirmed by the high correlations of dry days and total precipitation observed in this study (Figure 8a). In austral spring (SON), precipitation is higher in northeastern than in southwestern areas as also shown by Andrade (2018), which may be related to the later start of the rainy season in the southwestern areas.…”
Section: The Seasonal Cycle Of Precipitation and Temperaturesupporting
confidence: 86%
“…For total precipitation, recent studies focusing on similar areas found few significant trends and a high spatial variability for both annual and extended wet season time series (November–April) for slightly different periods within 1964 and 2013 (Haylock, 2006; Skansi et al ., 2013; Heidinger et al ., 2018; Huerta and Lavado‐Casimiro, 2020). Neukom et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations